Development of competency standards to inform intensive care nursing practice - Schmollgruber, Shelley (My University, 2015)
Purpose: The aim of this study was to explore and describe the components of best nursing practice in the care of acutely ill patients in the intensive care setting and to use this information to propose standards of competency for nursing care. The purpose was to inform responsibility and accountability in the intensive care setting, thereby contributing to excellent quality nursing care and improved patient outcome. Research method: The research method was structured in accordance with the process required to formulate nursing standards and comprised two phases, the developmental phase and the standards generation phase. Data collection: Data were collected during the developmental phase through the use of quantitative and qualitative methods. The study design was exploratory, descriptive and standards generative. Data collection was conducted using steps. Step 1, involved exploring and describing the clinical profile of critically ill patients and requirements for nursing care in the intensive care unit (n=4). This was achieved by means of a prospective, longitudinal, quantitative study. Steps 2 to 3, involved exploring the competencies nurses require in the provision of patient care in the intensive care units, which was achieved by means of an in-depth qualitative study. Unstructured interviews were held with a group of specialist nurses (clinical nurses, educators and facilitators) to elicit competencies that critical care nurses required in the provision of care. In step 3, a focus group was used to elicit the opinions of other nurse practitioners in the intensive care units as to which competencies they required or felt are used in the intensive care unit. Standards were generated during the standards generation phase. Step 4, involved compiling a set of preliminary competencies based on evidence generated in steps 2 and 3. Step 5 involved triangulation of the data obtained in the study. This was done by means of a literature review. Step 6 involved the generation of concept standards based on the information obtained in steps 1, 2, 3, and 4. Step 7, involved the validation of construct standards by means of a workshop with experts. Data analysis included descriptive statistics, content analysis, identification of themes and inductive and deductive logic. Conclusion: The conclusion included the recommendations of guidelines for the use of standards which was conducted in step 8. Context of the study: The setting for the study was four intensive care units at a university-affiliated, public sector and tertiary level health care institution in Gauteng Province, South Africa.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements of the degree of Doctor of Philosophy. Johannesburg, 2015